Market Orientation Drives Competitive Edge and Performance in Indonesian MSMEs: Orientasi Pasar Mendorong Keunggulan Kompetitif dan Kinerja UMKM Indonesia - Ainnia Dewi Oktaviah; Dewi Komala Sari (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of Product Innovation and Market Orientation on Marketing Performance, with Competitive Advantage as an intermediate variable, among MSMEs in Desa Kejapanan, Gempol. Using a sample of 70 respondents and analyzing data with Path Analysis via SmartPLS 3.0, the findings reveal that Product Innovation positively but insignificantly affects Marketing Performance, whereas Market Orientation has a significant positive impact. Both Product Innovation and Market Orientation significantly enhance Competitive Advantage, which in turn significantly improves Marketing Performance. The results underscore the importance of customer-oriented strategies and quality product innovations for better marketing outcomes. Future research should include variables like Digital Marketing and Social Media Advertising to further explore marketing performance improvements. Highlights: 1. Market Orientation: Significantly boosts Competitive Advantage and Marketing Performance.2. Product Innovation: Positively affects Marketing Performance, not significantly.3. Future Research: Include Digital Marketing and Social Media Advertising variables. Keywords: Product Innovation, Market Orientation, Marketing Performance, Competitive Advantage, MSMEs